Angklung sebagai Warisan Budaya Sunda: Kajian Fungsi, Nilai, dan Perkembangannya di Jawa Barat - Salsabila Barokatu Lana; Imam Amahdi; Nabilah Nurul Izzah; Nanda Rizky Julian Nugraha; Syairul Bahar; Farhan Abdurrochim Alfaruq (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
Angklung is one of the traditional musical instruments originating from the Sundanese culture in West Java, Indonesia, and has been recognized as an Intangible Cultural Heritage by UNESCO since 2010. This research aims to analyze the functions, values, and development of angklung in West Java society. The study applies a qualitative descriptive approach through literature review, field observations, and interviews with cultural practitioners. The findings show that angklung plays an important role not only as a musical medium but also as a tool for social cohesion, educational development, and cultural identity preservation. Over time, angklung has experienced significant transformation in terms of performance, musical arrangements, and adaptation in modern contexts, such as tourism, creative industries, and international collaborations. However, challenges remain in maintaining authenticity amid commercialization and the declining interest of younger generations in traditional musical arts. This study highlights the need for continuous cultural education, community engagement, and government support to sustain angklung's legacy. The implications of this study contribute to cultural preservation strategies and provide insights into the sustainable development of traditional arts in the modern era.